SURVIVAL HANDBOOK : AN ESSENTIAL COMPANION TO THE GREAT OUTDOORS - Sumerak, Marc (Becker&Mayer! kids, 2019)
This book includes crucial tips on exactly what you need to know to survive even the most unexpected circumstances. This illustrated guide shows you how to make a shelter, build a fire, locate clean water, forage for food, avoid deadly animals, protect yourself from bad weather, and find your way back home safely afterward. Whether you're lost, hungry, burned, or buried, knowing essential emergency survival skills could literally mean the difference between life and death